Hydrogen Degassing in a Vacuum Arc Degasser Using a Three‐Phase Eulerian Method and Discrete Population Balance Model. Issue 5 (6th April 2018) - Karouni, Faris; Wynne, Bradley P; Talamantes‐Silva, Jesus; Phillips, Stephen
Abstract : A three‐phase Eulerian model incorporating slag‐steel interactions to predict the rate of hydrogen removal from molten steel in a full‐scale industrial vacuum arc degasser (VAD) has been developed. The interfacial area for hydrogen transfer is calculated using a bubble population balance model. This accounts for bubble growth due to changes in hydrostatic pressure as well as coalescence and breakup. The predicted velocity field and bubble distribution are compared with experimental data in the literature. The bubble size predictions under atmospheric pressure conditions are sensitive to the initial bubble size, while under vacuum conditions they are relatively independent of the initial size. The omission of the slag layer from the model results in a 12% increase in the hydrogen removal rate. Variation in the slag eye diameter as a function of argon flowrate is simulated and compared with empirical correlations in the literature. Hydrogen measurements from a full‐scale VAD unit at Sheffield Forgemasters International Ltd. steelworks are compared to the model predictions for a series of melts of varying initial hydrogen content. Based on the initial hydrogen content of the liquid steel, the model predicts the amount of hydrogen removed to within ±20% of final experimental measurements obtained from the melt. Abstract : A mathematical model is developed to predict the rate of hydrogen removal during vacuum arc degassing. The Eulerian multiphase CFD approach is coupled to a population balance model. The resolved bubble‐liquid surface area is utilized in a mass transfer model. The importance of incorporating the slag layer in the fluid dynamic analysis is highlighted.